Macroalgae Improve the Growth and Physiological Health of White Shrimp (Litopenaeus vannamei) - Zhuofan Zhang; Xiaohui Shi; Zijie Wu; Wenbo Wu; Qun Zhao; Erchao Li (Aquaculture Nutrition)
This study compared and evaluated the effects of nine native macroalgae species on the tropic coast of China on the growth and physiological health performance of white shrimp (Litopenaeus vannamei). Nine hundred juvenile shrimps weighing 1.6±0.02 g were fed with nine different types of macroalgae for 28 days. The experimental groups were as follows: Con (the diet without macroalgae), CRA (Caulerpa racemosa), CLA (Caulerpa lentillifera), CSS (Caulerpa sertularioides), CLM (Chaetomorpha linum), ULA (Ulva lactuca), GBE (Gracilaria bailiniae), ASA (Acanthophora spicifera), SVC (Sargassum ilicifolium var. conduplicatum), and BGE (Betaphycus gelatinae). Results showed that the growth performance of shrimps fed on the macroalgae meals was significantly higher than that of the control group (P<0.05). The immune defense capacity (total hemocyte count, phagocytosis respiratory bursts, prophenoloxidase system, hemagglutination activity, and antibacterial and bacteriolytic activities) and antioxidant capacity (total antioxidant capacity, superoxide dismutase, catalase, glutathione peroxidase, and malondialdehyde) of L. vannamei fed on macroalgae meals were significantly higher than those of the control group (P<0.05). Specifically, the shrimps in the ASA group had the significantly higher physiological health level than shrimps in the other macroalgae groups (P<0.05), and the expression of immune and antioxidation-related genes was also significantly higher in the ASA group (P<0.05). Principal component analysis (PCA) demonstrated that optimal growth and physiological health efficacy were observed in the ASA group. In summary, this study suggested dietary manipulation using macroalgae to improve the growth performance, immune performance, and antioxidant capacity of L. vannamei, with the optimal macroalgae for the diet being Acanthophora spicifera.